2019
DOI: 10.1002/jib.569
|View full text |Cite
|
Sign up to set email alerts
|

Pre-fermentation with lactic acid bacteria in sour beer production

Abstract: Sour beer is beer with an intentionally sour taste. In traditionally produced sour beer, the acidic character results from spontaneous, mixed fermentation where different bacteria and yeast species participate. These complex fermentations take years to complete and can be difficult to control. Owing to the increasing interest in sour beer and challenges related to commercial sour beer brewing, alternative production methods are being explored. In the current paper, pre‐fermentation with lactic acid bacteria (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…In a previous study we have tested for an eventual pH-effect by adding lactic acid to wort prior to yeast fermentation. No effect by reduced fermentation pH (final beer pH 3.7) was found on ethanol production or ADF for the same yeast strain (Dysvik et al, 2019). These results suggest that the reduced performance by S. cerevisiae with respect to ethanol production and ADF in the L. brevis co-fermentation, was caused by some effects exerted by the presence of L. brevis itself.…”
Section: Beer Production Through Co-fermentationmentioning
confidence: 70%
See 1 more Smart Citation
“…In a previous study we have tested for an eventual pH-effect by adding lactic acid to wort prior to yeast fermentation. No effect by reduced fermentation pH (final beer pH 3.7) was found on ethanol production or ADF for the same yeast strain (Dysvik et al, 2019). These results suggest that the reduced performance by S. cerevisiae with respect to ethanol production and ADF in the L. brevis co-fermentation, was caused by some effects exerted by the presence of L. brevis itself.…”
Section: Beer Production Through Co-fermentationmentioning
confidence: 70%
“…Therefore, the objective of the current study was to investigate the effect of beer-related stress factors on growth and metabolite production by three different lactobacilli in wort medium. The selected strains were Lactobacillus brevis BSO464, a strain previously proven as resistant to the harsh beer environment (Bergsveinson et al, 2016); Lactobacillus plantarum (WildBrew TM Sour Pitch), a commercial brewing strain commonly used for kettle souring (biologic acidification of wort prior to yeast fermentation); and Lactobacillus buchneri CD034, a strain previously used in research on kettle souring (Dysvik et al, 2019) but originally isolated from silage grass (Heinl et al, 2012). Controlled co-fermentations with lactobacilli and Saccharomyces cerevisiae were evaluated as a time-saving method for sour beer production.…”
Section: Introductionmentioning
confidence: 99%
“…Saccharomyces, Zygosaccharomyces, and Lactobacillus dominant the baijiu fermentation stages. Similar to many other alcoholic beverages, such as wine and sour beer (Bartle et al, 2019;Dysvik et al, 2019), the production of miscellaneous baijiu seems also depend on the co-fermentation of lactic acid bacteria and yeasts. During wine fermentation, co-inoculation of lactic acid bacteria with yeast not only reduces the total acidity but also increases the ripe fruits notes associated with esters (Bravo-Ferrada et al, 2013).…”
Section: Association Between Microbial Community and Volatile Profilesmentioning
confidence: 99%
“…When the desired level of lactic acid has been obtained, the wort is then boiled to stop bacterial fermentation, followed by single-strain fermentation with conventional brewer's yeast. An alternative to the interfermentation boiling step is addition of highly hopped wort upon yeast addition to introduce antimicrobial iso-␣-acids after the wanted bacterial activity has transpired (112). In a study by Peyer et al (111), Lactobacillus amylovorus was used for biological acidification of mash and preboil and postboil worts.…”
mentioning
confidence: 99%
“…The authors showed how biological acidification at different time points in the preyeast fermentation process led to differences in the obtained beer product. Acidification of preboil wort emerged as an efficient method to ensure high acidity and minimal organoleptic failure (112). Prefermentation with Lactobacillus buchneri prior to yeast fermentation was tested for production of sour beer (112).…”
mentioning
confidence: 99%